(untitled) (Slavic Studies, 2024)
This article examines the contribution of Russian editions in the affirmation of Mаcedonian epigraphic wealth. Our focus is stress on eminent surdes, editions od Russian scientists that publish, document and interpret epigraphic monuments from Macedonia.